Exploring the gendered experiences of Australian tennis coaches: A cross-sectional survey of women and men tennis coaches - Petersen, J. M.; Pill, S.; Ridley, K.; Agnew, D.; Prichard, I. (Journal of Sports Sciences, 2024)
Women remain underrepresented in tennis coaching roles in Australia. This study aimed to examine the factors (barriers and facilitators) that may underlie gendered experiences in sport coaching and their links to retention in the profession, through the lens of Self-determination Theory. An online survey assessed barriers to coaching (individual, interpersonal, organisational and socio-cultural levels), coaching motivation and social support for coaching. Participants also completed measures of coach retention (coaching commitment, intentions to continue coaching). The survey was completed by 243 Australian tennis coaches (Mage = 49.5 ± 16.4 years, 35.8% women). The findings indicated that women coaches perceived experiencing significantly more socio-cultural barriers (e.g. discrimination, marginalisation) than their men counterparts. Fewer women (41.4%) than men (55.8%) intended to remain in the profession long-term (>10 years). Regression analyses did not reveal any predictors of retention among women coaches. In men, integrated regulation (ß = 0.22, p = .036) and amotivation (ß = -0.24, p = .010) predicted coaching commitment. Interpersonal barriers (OR = 0.27, p = .038), external regulation (OR = 0.68, p = .023) and amotivation (OR = 0.72, p = .040) predicted male`s intentions to exit the profession sooner. This study sheds light on the factors that shape the experiences of sport coaches. Ongoing efforts to support the retention of women in sport coaching are necessary and may include challenging socio-cultural barriers.